Internet Addiction Among Middle Eastern Students Significantly Impacts Mental Health : Kecanduan Internet di Kalangan Pelajar Timur Tengah Berdampak Signifikan pada Kesehatan Mental - Duha Abdul Rahman Mohammed; Hussein Alwan khalaf; Amal Roshdi Ahmed; Adnan Majeed Ghadeer (Academia Open, 2024)
Excessive internet use leads to problematic Internet usage (PIU), causing psychological, academic, and occupational issues. This study reviews 22 recent studies from PubMed, Google Scholar, and ResearchGate to assess internet addiction (IA) among Middle Eastern students and its link to anxiety and depression. The findings indicate a high prevalence of IA, significantly correlated with mental health disorders and negatively impacting academic performance. Enhanced assessment tools, a better understanding of IA's causes, and innovative interventions are needed to address this issue and mitigate its negative effects on students' mental health and academic outcomes. Highlight: High Prevalence: Internet addiction is common among Middle Eastern students. Mental Health Impact: Significant correlation between internet addiction, anxiety, and depression. Academic Decline: Internet addiction negatively affects students' academic performance. Keywoard: Internet addiction; mental health; academic performance; Middle Eastern students; anxiety